Psycho-demographic factors as predictors of sports leisure activities among students of Olabisi Onabanjo University - Adeleye, Adewale Olugbemiga; Okueso, Samuel Adesina; Abdul, Adekunle Adelaja; Balogun, Adeola Hannah (Journal of Education in Black Sea Region, 2022)
This study aimed to discuss psycho-demographic factors as predictors of sports leisure activities among selected students of Olabisi Onabanjo University. A descriptive survey research design of a correlational type was used for the study. The sample included 262 students from various faculties. Self-structured research instruments PFALQ: r=0.71 and DVILQ: r=0.76 were used for data collection. The data were analyzed using multiple regression. The result reveals a significant joint contribution of the independent variables on sports leisure activities. The result also shows the relative contribution of independent variables (motivation, self-esteem, personality, age, gender and religion) to the dependent variable (involvement in sports leisure activities. The findings revealed that was a joint contribution of psychodemographic status to leisure activities among selected students of Olabisi Onabanjo University. It was recommended that students should be informed of the benefits of participation in leisure activities.